Caracterização de uma célula tubular piezoelétrica para geração de energia elétrica - Rangel, Renato Franklin (2014)
Currently possible solutions for alternative electric power generation have been the subject of interest of many researchers. Many of these studies focus on the use of natural resources, theoretically inexhaustible, to preserve exhaustible sources of energy. More recently, it has been studied the possibility of generating low power electricity, but enough to meet the demand of some electronic systems. Systems such as wireless sensors or remote communication which has low power consumption can be benefited. Among various technologies for producing alternative electricity, the use of vibratory energy and deformation of structures can be used to generate electricity. This conversion has the piezoelectric materials that convert mechanical strain energy into electrical energy. Thus, this work presents the characterization study of a piezoelectric material, Lead Zirconate Titanate (PZT), with the purpose of generating electricity. For the characterization experiment, we used a cylindrical PZT subjected to compression in a cyclic manner in the axial direction. An experimental apparatus was designed and instrumented to capture the force, acceleration, voltage and electric power generated due to piezoelectric cell. Initially simulations were developed in order to guide the experimental set of actions. From the experimental results with a piezoelectric cell a piezoelectric generator was designed with three cells and characterized. Results of the physical parameters related to characterization are presented.